Sex Scene Media and the Sexual Revolution - Schaefer, Eric (Duke University Press, 2014)
Sex Scene suggests that what we have come to understand as the sexual revolution of the late 1960s and early 1970s was actually a media revolution. In lively essays, the contributors examine a range of mass media-film and television, recorded sound, and publishing-that provide evidence of the circulation of sex in the public sphere, from the mainstream to the fringe. They discuss art films such as I am Curious (Yellow), mainstream movies including Midnight Cowboy, sexploitation films such as ;Mantis in Lace, the emergence of erotic film festivals and of gay pornography, the use of multimedia in sex education, and the sexual innuendo of The Love Boat. Scholars of cultural studies, history, and media studies, the contributors bring shared concerns to their diverse topics. They highlight the increasingly fluid divide between public and private, the rise of consumer and therapeutic cultures, and the relationship between identity politics and individual rights. The provocative surveys and case studies in this nuanced cultural history reframe the "sexual revolution" as the mass sexualization of our mediated world.Contributors. Joseph Lam Duong, Jeffrey Escoffier, Kevin M. Flanagan, Elena Gorfinkel, Raymond J. Haberski Jr., Joan Hawkins, Kevin Heffernan, Eithne Johnson, Arthur Knight, Elana Levine, Christie Milliken, Eric Schaefer, Jeffrey Sconce, Jacob Smith, Leigh Ann Wheeler, Linda Williams